Turkish version of the Ureteral Stent Symptoms Questionnaire: linguistic and psychometric validation - TANIDIR, YILÖREN (SPRINGER, 2017)
Purpose Ureteric stents are frequently used in urology practice and can cause significant impairment in quality of life (QoL). The aim of this study was to validate the Ureteral Stent Symptoms Questionnaire (USSQ) to be used in the evaluation of stent-related symptoms and impairment in QoL in Turkish-speaking patients. Methods After linguistic validation of the original USSQ into Turkish language, the Turkish version of the USSQ (T-USSQ) was self-administered to all participants at week 1 and 4 after stent placement for test-retest reliability and internal consistency and at week 8 (4 weeks after stent removal) for sensitivity to change analysis. Control patients completed the form only once. Additionally male and female patients completed the validated Turkish versions of International Prostate Symptom Score (IPSS) and Marmara Overactive Bladder (mOAB) Symptom Scores, respectively. Results A total of 68 patients with ureteral stents and 37 controls were available for the final analysis. The Cronbach's alpha value was higher than 0.7 at week 1 for all sub-domains except additional problems domain. The test-retest reliability of the T-USSQ was high for all subdomains except the additional problems domain. Relatively high correlation coefficients were found for the visual analog scale for pain, IPSS (for males), mOAB score (for females) with the corresponding USSQ domains, suggesting good convergent validity. Also the T-USSQ could effectively differentiate between patients and controls. Conclusions The T-USSQ is a reliable and robust instrument that can be self-administered to patients of Turkish population with ureteral stent in the clinical applications.
Keywords: Ureteral stent; Symptom score; Questionnaire; Validation; QUALITY-OF-LIFE